2019
DOI: 10.21873/anticanres.13155
|View full text |Cite
|
Sign up to set email alerts
|

Para-aortic Lymph Node Invasion in High-risk Endometrial Cancer: Performance of 18FDG PET-CT

Abstract: Aim: 18 F-Fluorodeoxyglucose positron-emission tomography integrated with computed tomography ( 18 FDG PET-CT) is a non-invasive examination that could be helpful for the management of endometrial cancer. This study investigated the performance of 18 FDG PET-CT in assessing para-aortic (PA) lymph-node involvement in high-risk endometrial cancer. Materials and Methods: This was a retrospective, single-center study carried out between 2009 and 2018. The inclusion criteria were high-risk and locally advanced type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Its moderate sensitivity for detecting lymph node metastases during preo-perative staging probably reflects the need for a sufficient number of neoplastic cells to induce 18 F-fluoro-2-deoxy-D-glucose hypermetabolism. [89][90][91][92][93][94][95][96][97][98][99][100] The usefulness of maximal standardized uptake value in classifying patients into predefined risk groups is limited. 101 A pre-operative CT scan has a clinical utility in patients with endometrial carcinoma in detecting metastatic disease.…”
Section: Pre-and Intra-operative Work-upmentioning
confidence: 99%
“…Its moderate sensitivity for detecting lymph node metastases during preo-perative staging probably reflects the need for a sufficient number of neoplastic cells to induce 18 F-fluoro-2-deoxy-D-glucose hypermetabolism. [89][90][91][92][93][94][95][96][97][98][99][100] The usefulness of maximal standardized uptake value in classifying patients into predefined risk groups is limited. 101 A pre-operative CT scan has a clinical utility in patients with endometrial carcinoma in detecting metastatic disease.…”
Section: Pre-and Intra-operative Work-upmentioning
confidence: 99%
“…This false negative rate, which is partly related to the spatial resolution of PET-CT, ranges from 10% to 23% in cervical cancer [32,33]. In a study conducted by our team, we found a 20% false negative rate when PET-CT was used for lymph node evaluation in endometrial cancers [22]. This is a PET-CT-specific and cancer-independent limit.…”
Section: Studymentioning
confidence: 77%
“…Positron emission tomography/computed tomography (PET-CT) after 18FDG injection has been shown to be appropriate for lymph node evaluation in early-stage ovarian cancer [20], locally advanced cervical cancer [21], and high-risk type 1 endometrial cancer [22]. Within our center, we have been using PET-CT for many years in the management of EOC for both the initial extension work-up and the evaluation of the response to chemotherapy instead of the thoraco-abdomino-pelvic CT scan (TAP CT).…”
Section: Introductionmentioning
confidence: 99%
“…A previous single-center study found 100% specificity and a positive predictive value with a 92.9% accuracy rate for FDG-PET/CT for the evaluation of para-aortic involvement, particularly in high-risk histological type 1 endometrial cancers [9]. FDG-PET/CT performance was lower in type 2, with an increased risk of false negatives [9]. However, the results were not significant due to a low number of patients and a lack of power and need to be re-evaluated in a larger population.…”
Section: Introductionmentioning
confidence: 94%